New Generating Function Relations for the q-Generalized Cesàro Polynomials - Nejla Özmen (Journal of Function Spaces)
The main purpose of this paper is to examine a basic (or q-) analogue of the generalized Cesàro polynomials described here. We derive a bilateral q-generating function involving basic analogue of Fox’s H-function and q-generalized Cesàro polynomials.